2014
DOI: 10.1021/cs5008014
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Catalytic Activity of High-Index Faceted Palladium Nanoparticles in Suzuki–Miyaura Coupling Due to Efficient Leaching Mechanism

Abstract: The structure−property relationship of palladium (Pd) catalysts in Suzuki−Miyaura cross-coupling reactions was investigated using Pd nanocrystals of uniform size and shape. Superior catalytic reactivity was observed for Pd nanoparticles with high-index {730} surface facets compared to low-index {100} facets. Although the nanocrystal morphologies were maintained during the reaction, the presence of Pd clusters, identified by high-resolution transmission electron microscopy (TEM), indicates a leaching mechanism.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
69
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(71 citation statements)
references
References 57 publications
1
69
0
1
Order By: Relevance
“…Pd-NPs are a very important class of catalyst for numerous organic transformations. Among others, the Suzuki-Miyaura cross-coupling reaction between various organic halides and boronic acids is arguably the most valuable reaction for synthetic chemists [24][25][26][27]. The Pd-NP/polythiophene nanospheres contain sub-20 nm Pd-NPs which are known to be very effective catalyst for Suzuki-Miyaura cross-coupling reaction under mild reaction conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pd-NPs are a very important class of catalyst for numerous organic transformations. Among others, the Suzuki-Miyaura cross-coupling reaction between various organic halides and boronic acids is arguably the most valuable reaction for synthetic chemists [24][25][26][27]. The Pd-NP/polythiophene nanospheres contain sub-20 nm Pd-NPs which are known to be very effective catalyst for Suzuki-Miyaura cross-coupling reaction under mild reaction conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The Pd-NP/polythiophene nanospheres contain sub-20 nm Pd-NPs which are known to be very effective catalyst for Suzuki-Miyaura cross-coupling reaction under mild reaction conditions. For instance, Collins and co-workers recently reported Pd-NP shape-/size-dependent catalytic activities for SuzukiMiyaura cross-coupling reaction, comparing the catalytic activities of 10 nm and 20 nm cube-shaped Pd-NPs and concave cubic Pd-NPs with faceted with high-index {730} facets with a dimension similar to 20 nm Pd-NP cubes [24]. Interestingly, 20 nm Pd-NP (0.5 mol%) did not exhibit any catalytic activity for a prolonged reaction period ($30 h) under very similar reaction conditions compared to this study.…”
Section: Resultsmentioning
confidence: 99%
“…NPs with high index surface facets were also useful catalytic probes for Suzuki coupling. [13] Concave Pd nanocubes exhibited a nearly 7-fold increase in the surface normalized turn over frequency compared to the cubic counterparts. Analysis of the catalysts post reaction showed that the structural integrity of the concave catalysts appeared well preserved at high catalysts loadings, but only at lower catalysts loadings was dissolution of the NP and morphological evolution to small diameter NPs was apparent as shown in Figure. 1 (e)-(h).…”
Section: Designing Catalytic Nanoparticles To Probe Reaction Mechanismsmentioning
confidence: 97%
“…According to Gaikwad et al [56] Pd 0 atom and Pd II ion leach simultaneously and this simultaneous leaching underpins the catalysis in the SMXR. High-index surface facets have also been correlated with high catalytic activity as a result of increased Pd leaching [57,58].…”
Section: The Mechanism Of Catalysis By Nanoparticles-on the Surface Omentioning
confidence: 99%